Formulation and Characterization of Glucosamine Sulphate Potassium Chloride (GSPC) Loaded Emulgel for the Treatment of Osteoarthritis - Rao, Komal; Kumari, Shalini; Minocha, Neha (Current Rheumatology Reviews, 2025)
BackgroundOsteoarthritis (OA) is becoming a major medical burden worldwide due to changing lifestyles and aging populations. Osteoarthritis is a disease characterized by a variety of anatomic and physiological changes to joints, including cartilage degradation, bone remodeling, and the formation of osteophytes. These changes cause pain, stiffness, swelling, and limitations in joint function. Glucosamine serves as a fundamental constituent for cartilage, the resilient connective tissue responsible for cushioning joints. Glucosamine Sulphate Potassium Chloride (GSPC) supplementation is widely employed to mitigate symptoms linked to osteoarthritis, a degenerative joint disorder hallmarked by cartilage degradation.AimPalliative care aims at minimizing pain and disability and improving function, performance, and quality of life. In this study, the emulgel formulation of GSPC was developed and checked for its potential.ObjectiveCurrently, OA does not have a definitive treatment. Since conventional dosage forms cannot deliver the active drug content at a predefined target site in a predictable manner throughout the treatment period, a new carrier system is always required. Considering their reduced size, targeting potential, and site specificity, nanocarrier-based approaches could hold an answer to shortcomings associated with conventional routes. Thus, the objective of the current study was to formulate and characterize glucosamine sulphate potassium chloride-loaded emulgel for the treatment of osteoarthritis.MethodsMicroemulsion of glucosamine sulphate potassium chloride was formulated using a spontaneous emulsification method comprising of oleic acid (oil phase), Tween 80, Tween 20 (surfactant) and PEG 400, Span 80 (co-surfactant), and distilled water (aqueous phase). The microemulsions were evaluated for surface morphology, globule size, poly-dispersibility index (PDI), zeta potential, and viscosity, and the final batch of microemulsions was selected.ResultsThe optimized microemulsion contained 35% co-surfactant (propylene glycol), 20% surfactant (Tween 20), and 15% oil (oleic acid) and glucosamine sulphate potassium chloride in a dose of 60 mg, which has sufficient drug loading capacity with a droplet size of 182 nm for optimized formulation. The optimized microemulsion formulation was added to gel prepared by Carbopol 934 in a 1:1 (w/w) ratio, leading to the formulation of glucosamine sulphate potassium chloride-containing emulgel. The prepared emulgel was further evaluated for viscosity, drug content, pH, and in vitro drug release. Emulgel formulation (F6) showed 88% drug release after 6 hours, and it followed the Higuchi model.ConclusionGlucosamine Sulphate Potassium Chloride (GSPC) is used in the treatment of OA by increasing the production of proteoglycans, which can cause the cartilage to break down. Emulgel formulation (F3) showed 75.41% drug release, and formulation (F6) showed 88% drug release after 6 h. Therefore, it may be concluded that an emulgel of GSPC can be used as a controlled-release dosage form of the drug for local application in OA.
Keywords: Emulgel